Geospatial Data Quality: Guidelines and Procedures - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
In this document, the term ‘geospatial data’ is used to refer to data that provides information on the location of features, attributes, and often temporal information as well. Different types of geospatial data can be produced for different purposes and through different processes.